European conference on urban innovations : Seville, 6-8 October 1993. (Office for Official Publications of the European Communities, 1994)
The Conference took place in Seville in October 1993 and covered a wide range of innovations, in such areas as environmental auditing, urban transport, housing and urban regeneration. The projects were discussed in terms of sustainability, and placed within a wider European and international context. The major themes which emerged, and which will be given priority, relate to environmental auditing in cities, urban innovation and employment generation, and the functionality and aesthetics of large urban spaces. As well as the Conference papers, this publication includes additional relevant materials. It should be read in conjuction with the European overview published in 1993, because the projects surveyed by the overview formed the backbone of the Seville Conference, providing its particular focus and flavour.